2011
DOI: 10.1590/s1677-55382011000100010
|View full text |Cite
|
Sign up to set email alerts
|

Reducing infectious complications after transrectal prostate needle biopsy using a disposable needle guide: is it possible?

Abstract: Purpose: To investigate whether the use of a disposable needle guide results in a decreased incidence of infectious complication after transrectal prostate needle biopsy (TPNB). Materials and Methods: Fifty five patients who underwent 10-core TPNB were randomized into two groups. A pre-biopsy blood and urine examination was performed in both groups. Group 1 (25 patients) underwent biopsy with disposable biopsy needle guide and Group 2 (30 patients) underwent biopsy with reusable biopsy needle guide. All patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
0
5
1
Order By: Relevance
“…Tuncel et al [ 23 ] reported that the use of a disposable needle guide, compared to a reusable needle guide disinfected between patients, significantly reduced the number of fevers and urinary tract infections after biopsy [ 23 ]. These results were not supported by a later study by Gurbuz et al [ 24 ] who observed no difference. Both studies had similar antibiotic prophylaxis and disinfection regimes and it may be that the differences were due to technical differences in the model of needle guide used.…”
Section: Discussioncontrasting
confidence: 89%
“…Tuncel et al [ 23 ] reported that the use of a disposable needle guide, compared to a reusable needle guide disinfected between patients, significantly reduced the number of fevers and urinary tract infections after biopsy [ 23 ]. These results were not supported by a later study by Gurbuz et al [ 24 ] who observed no difference. Both studies had similar antibiotic prophylaxis and disinfection regimes and it may be that the differences were due to technical differences in the model of needle guide used.…”
Section: Discussioncontrasting
confidence: 89%
“… 24 However, a smaller prospective randomized study by Gurbuz et al found no difference in infectious outcomes. 25 …”
Section: Strategies For Preventing Pnb-related Infectionsmentioning
confidence: 99%
“…found that rectal cleansing with povidone-iodine can reduce infective complications after the biopsy,[ 36 ] while using disposable needle was not successful in diminishing it. [ 37 ] Studies about prebiopsy enema gave conflicting results. [ 38 39 ] Other studies gave a promising future for targeted prophylactic ABx.…”
Section: Discussionmentioning
confidence: 99%